The Effect of Orobanche crenata Infection Severity in Faba Bean, Field Pea, and Grass Pea Productivity - Fernández-Aparicio, Mónica; Flores, Fernando; Rubiales, Diego (Frontiers in Plant Science, 2016)
Broomrape weeds (Orobanche and Phelipanche spp.) are root holoparasites that feed off a wide range of important crops. Among them, Orobanche crenata attacks legumes complicating their inclusion in cropping systems along the Mediterranean area and West Asia. The detrimental effect of broomrape parasitism in crop yield can reach up to 100% depending on infection severity and the broomrape-crop association. This work provides field data of the consequences of O. crenata infection severity in three legume crops i.e. faba bean, field pea and grass pea. Regression functions modelled productivity losses and revealed trends in dry matter allocation in relation to infection severity. The host species differentially limits parasitic sink strength indicating different levels of broomrape tolerance at equivalent infection severities. Reductions in host aboveground biomass were observed starting at low infection severity and half maximal inhibitory performance was predicted as 4.5, 8.2 and 1.5 parasites per faba bean, field pea and grass pea plant, respectively. Reductions in host biomass occurred in both vegetative and reproductive organs, the latter resulting more affected. The proportion of resources allocated within the parasite was concomitant to reduction of host seed yield indicating that parasite growth and host reproduction compete directly for resources within a host plant. However, the parasitic sink activity does not fully explain the total host biomass reduction because combined biomass of host-parasite complex was lower than the biomass of uninfected plants. In grass pea, the seed yield was negligible at severities higher than 4 parasites per plant. In contrast, faba bean and field pea sustained low but significant seed production at the highest infection severity. Data on seed yield and seed number indicated that the sensitivity of field pea to O. crenata limited the production of grain yield by reducing seed number but maintaining seed size. In contrast, the size of individual parasites was not genetically determined but dependent on the host species and resource availability as a consequence of parasite competition at increasing infection severities.